Experimental histopathological study on retinal and renal cellular response to intravitreous antiangiogenic drugs - Fortes Filho, João Borges (International Journal of Ophthalmology Press, 2014)
AIM: To evaluate histopathological retinal and renal response after one single dose of intravitreous injection of antiangiogenic drugs ranibizumab and bevacizumab in rats. METHODS: Experimental study in 60d of life adults Wistar rats. Ten animals were included. Group 1 included 5 animals that were injected with 1 µL ranibizumab 1.25 mg in the right eye and with 1 µL of balanced salt solution (BSS) in the left eye, as control; Group 2 included 5 animals that were injected with 1 µL of bevacizumab in the right eye and with 1 µL of BSS in the fellow eye. All injections were performed with Hamilton syringes. After 15d of the interventions, all animals were sacrificed in CO(2) chamber. Both eyes were enucleated and one kidney was removed, fixed and embedded in paraffin for histopathological analysis by optic microscopy. For statistical purposes the initial expected abnormal histopathological responses were defined as 0%. RESULTS: Atypical histopathological retinal response was detected in 2 eyes injected with ranibizumab (40%) as well as in 2 control eyes in group 1. Same was detected in 1 eye injected with bevacizumab (20%) as well as in 1 control eye, in group 2. The noted atypical findings were lymphocytes and eosinophils in the vitreous posterior cavity and mild retinal inflammatory reaction with ganglion cell layer edema but without clinical significance. No atypical histopathological renal response was detected. CONCLUSION: Unexpected atypical histopathological retinal response without clinical significance was observed in 3 eyes injected with antiangiogenic drugs (2 in group 1 and 1 in group 2) as well as in 3 control eyes (2 in group 1 and 1 in group 2). No atypical renal response was detected suggesting no extra ocular involvement of the intravitreous injected antiangiogenic drugs.